Australian Network for Art and Technology - Australian Network for Art and Technology (Adelaide : Australian Network for Art and Technology, 1994)
Website of ANAT 'Australia's peak network and advocacy body for artists working with science and technology'. Contains administrative information, listings, online publications and examples of artworks.
Title from title screen (viewed on 9 August 2005)
Text, sound and images.
Mode of access: Internet via World Wide Web. Available at: http://www.anat.org.au
System requirements: Macromedia Flash player; Adobe Acrobat reader.
Selected for archiving
Keywords: Art and science; Art and technology; Computer art